Effects of increasing GleptoForte dosage in newborn pigs on sow and litter performance - Burton, Leeanna; Williams, Hayden E.; Jones, Cassandra K.; DeRouchey, Joel M.; Tokach, Michael D.; Woodworth, Jason C.; Goodband, Robert D.; Dritz, Steven S.; Holtcamp, A. (My University, 2017)
It is known that iron deficiency is common in newborn pigs, resulting in the practice of a 200mg iron injection within 3 days postpartum. This trial was to determine the effects on newborn pigs on sow and litter performance with an increasing dosage of Gleptoforte, focusing on body weight (BW), average daily gain (ADG), and blood criteria. Gleptoforte, a Ceva Animal Health product, is an iron injection containing gleptoferron which combats iron deficiency. This study utilized 336 newborn pigs (DNA 241 X 600; initially 3.83 ± 0.114lb BW), from 28 litters. There were six treatments: negative control receiving no injection, 50mg, 100mg, 150mg, 200mg, and 200mg + 100mg booster on day 11 of farrowing. At processing (approximately day 3 postpartum), six barrows and gilts from each litter were randomly assigned to a treatment, 56 pigs per treatment, and given their dosages. Blood collection via jugular venipuncture was collected from one randomly selected barrow from each treatment, per litter. Blood criteria included: Hemoglobin (Hgb), Hematocrit (Hct), Serum Fe, and Total Iron Binding Capacity (TIBC). Weights and blood were collected days 3, 11, and 21 (weaning). On day 21, BW of the 0mg treatment was 10.4lb and ADG was .32lb, resulting in the lowest growth performance. Alternatively, the 100mg treatment had a BW of 12.9lb and ADG of .45lb, resulting in the greatest overall growth performance. On day 21, the 200mg treatment had a BW of 12.7lb and ADG of .43, while the 200mg + 100mg booster had a BW of 12.6lb and ADG of .43lb, which proved nonsignificant. On day 3, blood criteria were similar across treatments, while on days 11 and 21 a treatment × day interaction was observed. On days 11 and 21 all blood parameters increased, with the 0mg treatment resulting in the lowest values. On day 21, a difference was observed for Hct, Hgb, and Serum Fe between the 200mg and 200mg + 100mg treatments with 200mg + 100mg resulting in the greatest values. An accepted alpha value of (P<0.005) was used for this trial. In summary, the poorest growth rate was seen in the pigs receiving no Gleptoforte injection, while the pigs receiving 100mg showed the greatest performance in growth. In addition, the 200mg and 200mg + 100mg treatments resulted in similar growth performances but 200mg + 100mg had better blood parameters. Ultimately the 100mg dosage outperformed the 200mg + 100mg dosage for BW and ADG.
Keywords: Fall 2017